Hubungan Efikasi Diri, Kualitas Tidur dan Motivasi Belajar dengan Tingkat Kecemasan Pada Mahasiswa yang Akan Menghadapi Ujian Mcq Tahap Akademik Fakultas Kedokteran Universitas Islam Al-Azhar - I Made Putra Satia Dharma; Ronanarasafa Ronanarasafa; Dany Karmila; Yolly Dahlia (Universitas Malahayati, 2026)
ABSTRACT Anxiety is an emotional condition characterized by feelings of worry or fear arising from thoughts or expectations. According to the 2020 Riskesdas, the prevalence of anxiety in Indonesia is approximately 6.1% among individuals aged 15 years and above. Anxiety is commonly experienced by university students, particularly medical students. Global data indicate that the prevalence of anxiety among medical students ranges from 29.2% to 38.7%. Anxiety in medical students is often associated with a heavy academic workload. One condition that frequently triggers anxiety is the period preceding MCQ examinations. This study aims to determine whether there is a relationship between self-efficacy, sleep quality, and learning motivation with the level of anxiety of academic stage students at the Faculty of Medicine, Al-Azhar Islamic University who will face the MCQ exam. This study employed a cross-sectional study design and was conducted at the Faculty of Medicine, Universitas Islam Al-Azhar in October 2025. The research sample consisted of 222 respondents. The instruments used were the DASS-42 questionnaire to measure anxiety levels, the GSES to assess self-efficacy, the PSQI to evaluate sleep quality, and the MSLQ to measure learning motivation. Data were analyzed using the Spearman rank correlation test with a significance level of p-value ≤ 0.05. Bivariate analysis showed a significant relationship between self-efficacy and anxiety levels (p-value = 0.000, correlation coefficient = 0.415), between sleep quality and anxiety levels (p-value = 0.000, correlation coefficient = 0.432), and between learning motivation and anxiety levels (p-value = 0.000, correlation coefficient = 0.224). There is a significant relationship between self-efficacy, sleep quality, and learning motivation with anxiety levels among medical students at Universitas Islam Al-Azhar who are facing MCQ examinations. Keywords: Anxiety Level, Self-efficacy, Sleep Quality, Learning Motivation. ABSTRAK Kecemasan merupakan kondisi emosional yang ditandai oleh perasaan khawatir atau takut yang muncul dari pikiran atau harapan. Menurut Riskesdas tahun 2020, prevalensi kecemasan di Indonesia sekitar 6,1% pada usia 15 tahun keatas. Kecemasan sering dialami oleh mahasiswa salah satunya mahasiswa kedokteran. Data global menemukan bahwa prevalensi mahasiswa kedokteran yang mengalami kecemasan sekitar 29,2% sampai 38,7%. Kecemasan pada mahasiswa kedokteran dikarenakan memiliki beban pelajaran yang tinggi. Kondisi yang sering memunculkan kecemasan yaitu menjelang ujian MCQ. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan efikasi diri, kualitas tidur, dan motivasi belajar dengan tingkat kecemasan mahasiswa tahap akademik fakultas kedokteran Universitas Islam Al-Azhar yang akan menghadapi ujian MCQ. Penelitian ini menggunakan desain studi cross sectional, dilakukan di Fakultas Kedokteran Universitas Islam Al-Azhar pada bulan Oktober 2025. Sampel penelitian sebanyak 222 responden. Alat ukur yang digunakan yaitu kuesioner DASS 42 untuk mengukur tingkat kecemasan, kuesioner GSES untuk mengukur efikasi diri, kuesioner PSQI untuk mengukur kualitas tidur dan kuesioner MSLQ untuk mengukur motivasi belajar. Data dianalisis dengan uji korelasi Rank Spearman dengan batas nilai signifikasi p-value ≤ 0,05. Hasil analisis bivariat mengenai hubungan efikasi diri dengan tingkat kecemasan didapatkan p-value 0,000 dan koefisien korelasinya sebesar 0,415, hubungan kualitas tidur dengan tingkat kecemasan didapatkan p-value 0,000 dan koefisien korelasinya sebesar 0,432, dan hubungan motivasi belajar dengan tingkat kecemasan didapatkan p-value 0,000 dan koefisien korelasinya sebesar 0,224. Terdapat hubungan signifikan antara efikasi diri, kualitas tidur dan motivasi belajar dengan tingkat kecemasan pada mahasiswa Universitas Islam Al-Azhar yang akan menghadapi ujian MCQ. Kata Kunci: Tingkat Kecemasan, Efikasi Diri, Kualitas Tidur, Motivasi Belajar.